Analisis Visual Sampul Album Trio Bimbo 1971 - Mochammad Raihan Lazuardi Imani raihan; Inko Sakti Dewanto (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
Bimbo is one of Indonesia's legendary pop bands, known for infusing meaningful life lessons into every piece of their work, including their 1971 album Trio Bimbo. This study analyzes the cover of Trio Bimbo's 1971 album as a representation of the visual identity of Indonesian pop music in the 1970s, comparing it to the cover design of Koes Plus's album from the same period. The methods used include visual-descriptive analysis to examine typography, illustrations, colors, and layout, as well as historical analysis to contextualize the work within the development of Indonesian music. The results show that the Trio Bimbo 1971 album cover features a minimalist visual style with strong cultural symbols, reflecting the simplicity and religious values characteristic of Bimbo. Theoretically, this research contributes to enriching graphic design studies from the perspective of Indonesian popular music history. Practically, the results of this research can serve as a reference for graphic designers and music curators in developing designs rooted in cultural identity.